Effectiveness of Digitized Care Continuum Program in a Multispecialty Hospital - Kolothodi, Devanand (Global journal of Business and Integral Security, 2025)
This study was conducted to assess the efficacy of digitized care continuum program in multispecialty hospital. The intervention was designed to improve communication, coordination and teamwork across healthcare sectors in order to provide smooth post-discharge patient care. Data from 500 patients were collected to evaluate the effect of the program on patient satisfaction, clinical outcomes, patient loyalty, reduction in readmission rates and workload. The Net Promoter Score (NPS) for patient satisfaction was 92, reflective of a very high level of positive interest in the program during the semi-structured interviews. Overall, the results indicated that patients were satisfied with their experience of continuity care despite a few neutral suggestions for improvement. According to the research, 47% of patients were loyal promoting retention and the remaining were between neutral feedback flagging a strategy for more patient engagement. The program also reduced readmission rates, exhibiting better clinical outcomes after discharge. A comparison of data from 2022 to mid-2023 found significant reductions in readmissions among patients treated through the program compared with those who were not enrolled. This highlights how the program effectively reduced readmissions. The program also had beneficial effects in all the clinical specialities promoting the widespread of use of such programs in multi-speciality hospitals. This improvement in clinical outcomes, patient satisfaction and retention visibly seen in all the clinical specialities underscore the fact that the usage of care continuum should not be limited to certain specialities. It also had a positive effect on employee workload, with 90% of staff reporting that their time could be spent more efficiently. The improvement was due to increased collaboration among healthcare workers and reduced paperwork because they used digital technology. However, 10% of employees thought that training and awareness can be improved indicating areas where targeted intervention could prove effective. According to the study, this digitized care continuum results in higher levels of patient satisfaction and clinical outcomes, productivity growth among staff as well as lower readmissions. To ensure optimal results, it is also crucial to continue training and customization while generating buy-in from staff members. On the basis of the preliminary results, future work should center on long-term benefits and be extended to other geographies with additional personalization and augmented training aimed at maximizing patient care quality.